Implementation Of Public Service Communication By The Lebak Regency Government Through The SP4N-Lapor! Application - Ida Nurul Fhatihah; Fitri Dwi Lestari (Asosiasi Dosen Muda Indonesia, 2026)
The advancement of information and communication technology has made it easier for society to interact without the limits of space and time. The utilization of technology in public services is essential to create participatory, accountable, and transparent services, as well as to support competitive government institutions. One of its implementations is the application of SP4N-LAPOR! in Lebak Regency. This application serves as a platform for citizens to convey aspirations and complaints online, integrated in a tiered system. This study aims to examine whether the implementation of SP4N-LAPOR! has met the expectations of both the government and the community. Using Everett M. Rogers’ Diffusion of Innovation theory with a descriptive qualitative method and a post-positivist paradigm, the findings indicate that SP4N-LAPOR! facilitates citizens in reporting and communicating with the government regarding development issues. The application accelerates the flow of information and enhances public involvement. However, socialization efforts need to be strengthened to optimize its utilization. Overall, the implementation of SP4N-LAPOR! has been running well and supports the improvement of public communication.